Decreasing Missed Appointments at a Community Health Center: A Community Collaborative Project. (June 2022) - Biggs, Jennifer; Njoku, Nnamdi; Kurtz, Kaitlyn; Omar, Ayan
Introduction: Missed appointments are a problem for health care systems, causing lost revenue and concern for poor health outcomes. This is particularly true at Community Health Centers (CHCs), where clients may already face substantial barriers to optimal care and outcomes. Identified solutions to this problem are limited, and often focus on reminder calls and messages to clients.Methods: This project utilized a unique academic/CHC collaboration to investigate and initiate solutions to their high missed appointment rates. Client phone calls to determine clinic specific needs, monthly team meetings to brainstorm and choose initiatives, engaging stake holders, and phased implementation were the tools used to address the high missed appointment rates within the limitations of the clinic resources available.Results: Within one quarter, missed appointment rates at the clinic dropped by 6%-17% for different appointment types.Conclusion: While the project was interrupted due to the pandemic, early outcomes were promising and the model may be helpful to other CHCs with similar concerns.